2020
DOI: 10.1093/ckj/sfaa086
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of hemodialysis patients infected with severe acute respiratory syndrome coronavirus 2 and impact of proactive chest computed tomography scans

Abstract: Background Coronavirus disease 2019 (COVID-19) is an emerging infectious disease that first manifested in humans in Wuhan, Hubei Province, China, in December 2019, and has subsequently spread worldwide. Methods We conducted a retrospective, single-center case series of the seven maintenance hemodialysis (HD) patients infected with COVID-19 at Zhongnan Hospital of Wuhan University from 13 January to 7 April 2020 and a proactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…This hyper-inflammatory storm may play a role in the tissue damage and death of patients [4,48]; however, this response is blunted in infected HD patients. Several studies have revealed leukopenia, lymphopenia, lower serum calcium concentration, and elevated CRP levels in HD patients; however, other researchers have failed to find changes in numbers of granulocytes or lymphocytes in infected HD patients [17][18][19]21,22]. Ma Y et al found that the counts of T cells, CD4 T cells, CD8 T cells, natural killer cells, and B lymphocytes were reduced in the peripheral blood of infected HD patients compared with non-HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This hyper-inflammatory storm may play a role in the tissue damage and death of patients [4,48]; however, this response is blunted in infected HD patients. Several studies have revealed leukopenia, lymphopenia, lower serum calcium concentration, and elevated CRP levels in HD patients; however, other researchers have failed to find changes in numbers of granulocytes or lymphocytes in infected HD patients [17][18][19]21,22]. Ma Y et al found that the counts of T cells, CD4 T cells, CD8 T cells, natural killer cells, and B lymphocytes were reduced in the peripheral blood of infected HD patients compared with non-HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, COVID-19-related kidney injury may also aggravate heart failure. (3) Both the development of kidney injury in the course of COVID-19 as well as pre-existent CKD not on dialysis or on RRT by kidney transplantation (Tx), HD or PD are associated with an increased risk of death [ 11 , 43 , 44 ]. Thus prevention strategies should be emphasized in HD patients and also in PD patients and kidney transplant programmes should be stopped at the peak of the pandemic [ 39–42 , 49 ].…”
Section: Electrolyte Abnormalities and Kidney Injury In Covid-19mentioning
confidence: 99%
“…Wang et al . (Wuhan, China) [ 44 ] report on 7 of 202 HD patients diagnosed with COVID-19 at a mean age of 59 years, thus a different patient population from the Italian series. Computed tomography scan was used as a screening method for the whole HD population and bilateral ground-glass lung opacities and consolidation were the most common radiologic findings.…”
Section: Covid-19 and Ckd And Chronic Rrtmentioning
confidence: 99%
“…Considering the pathogenesis of lung involvement findings in COVID-19 infection and changes in the immune system response in HD patients, it is not known whether the frequency of lung involvement findings will differ in this group of patients. In the study by Wang et al (14), bilateral diffuse consolidation or groundglass appearances were observed in all 7 HD patients who were diagnosed with COVID-19, and death was reported in 3 of the patients. In the study of Du et al (11) with 32 COVID-19 positive HD patients, ground-glass opacities were observed in 18 cases; unilateral consolidations were observed in 7 patients, bilateral consolidations were observed in 7 patients; and pleural effusion was observed in 2 patients.…”
Section: Discussionmentioning
confidence: 92%